Finite element analysis of lumbar spinal cord for wearers of highheeled footwear / Milad Sabbagh - Milad, Sabbagh (2012)
It has already been reported by many researches about the possible negative effects due to wearing high heel shoes including, feeling pain in lower part of the back due to curvature increment of spinal, and feeling foot pain as consequent of placing more weight and finally more pressure on the toe feet. The objective of recent study is to investigate the stress distribution on lumber intervertebral disc of L4/L5 using a three dimensional finite element analysis during standing on high heels with three different heights. Therefore, a 3D finite element model of Functional Spine Unit (FSU) including L4, L5 and intervertebral disc was generated based on MRI scan files of a young female which was further modified in CATIA CAD modeling software and meshed and loaded in ANSYS finite element analysis software. Simulation results yielded a compression stress distribution of 3 MPa due to bending of forward flexion of FSU and downward displacement of 2 mm due to using elevated shoes with 8 cm height. Clinical concerns with prolonged standing on high elevated shoes with 8 cm height would be addressed to disc thinning observed in simulation results of the current study which can be resulted in low back pain. Therefore avoiding of prolonged standing on the high elevated shoes is advisable.